2017
DOI: 10.3390/bs7020034
|View full text |Cite
|
Sign up to set email alerts
|

Social Support, Religious Involvement and Alcohol Use among Students at a Conservative Religious University

Abstract: The misuse of alcohol among college students remains a significant public health concern in the United States. Excessive drinking among college students has been linked to numerous negative consequences, including rape, impaired academic performance, absenteeism from work and school and damaged social relations. This study examined whether religious involvement and social support played a role in reducing the frequency of alcohol use. A non-random convenience sample of 364 students from a larger study of 760 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…Although the role of religion as a protective mechanism among international students has received some scholarly attention (e.g., Hsu et al, 2009), the stress-buffering benefits of religion and spirituality afforded to diverse immigrant populations has been widely discussed (e.g., Hodge, Cardenas, & Montoya, 2001;Hsu et al, 2009). Among U.S. college students, religion is associated with reduced alcohol use (Galen & Rogers, 2004;Thompson, 2017). Given the positive association that emerged between religious affiliation and resilience in the current study, the findings converge to tentatively suggest that religiosity may mitigate the stressors that render some international students vulnerable to binge-drinking behavior.…”
Section: Binge Drinkingsupporting
confidence: 50%
“…Although the role of religion as a protective mechanism among international students has received some scholarly attention (e.g., Hsu et al, 2009), the stress-buffering benefits of religion and spirituality afforded to diverse immigrant populations has been widely discussed (e.g., Hodge, Cardenas, & Montoya, 2001;Hsu et al, 2009). Among U.S. college students, religion is associated with reduced alcohol use (Galen & Rogers, 2004;Thompson, 2017). Given the positive association that emerged between religious affiliation and resilience in the current study, the findings converge to tentatively suggest that religiosity may mitigate the stressors that render some international students vulnerable to binge-drinking behavior.…”
Section: Binge Drinkingsupporting
confidence: 50%
“…Other studies have shown that subjects with higher levels of religiosity tend to have a more orderly life and behave more prudently [66,67]. Some authors have explained this effect as being due to the influence of peers, as well as the control/protection exercised by the religious community [68]. However, after the other variables were adjusted for, the effect was only maintained in male students, which has not been mentioned in previous studies.…”
Section: Discussionmentioning
confidence: 68%
“…30 A similar case was also observed in the USA at Conservative Religious University. 40 The aforementioned studies explained peer influences were associated factors for young peoples’ involvement in substance use; however, these studies did not specify which type of substances young people involved in.…”
Section: Discussionmentioning
confidence: 99%
“…As far as parental influences are concerned, studies conducted in universities of North India, 23 in Poland, 39 and in Conservative Religious University of USA 40 also indicated young people involved in substance use because of parental influences. In particular, young people in northern Thailand are involved in alcohol use because of parental influences.…”
Section: Discussionmentioning
confidence: 99%